Tunable structural color with gradient and multiaxial polydimethylsiloxane wrinkling - Tan,A; Pellegrino,L; Ahmad,Z; Cabral,JT (Advanced Optical Materials, 2022)
The generation of structural color from wrinkled polydimethylsiloxane (PDMS) surfaces, fabricated by plasma exposure, subjected to uni- and multi-axial, and sequential strain fields is examined. The approach is based on the well-known, mechanically-induced, buckling instability of a supported bilayer, whereby the top glassy “skin” is formed by plasma oxidation. Surface periodicities 200 nm d 3 μm, encompassing the visible spectrum, are investigated in terms of the observed color, intensity spectrum, and color mixing from different diffraction orders, exhibiting good agreement with model predictions. By contrast with complex fabrication methods, color tunability and mechanochromic response are readily achieved by adjusting plasma and strain parameters, and by dynamically varying strain (ε 50%). Prescribed strain directionality, employing uniaxial, isotropic, gradient strain, and wave-sum wrinkling superposition, as well as skin thickness (and thus d) and amplitude gradients, using facile and scalable fabrication approaches, yield striking spatial color variation, homogeneity, and directionality.